SOCIAL RESILIENCE OF SMALL SCALE FISHERMAN HOUSEHOLDS AND ITS INFLUENCING FACTORS IN BENGKULU CITY - Fitria, Pebi; Cahyadinata , Indra; Mulyasari, Gita; Nurjati, Eka (Jurnal Perikanan Unram, 2025)
Small-scale fishers in Bengkulu City play an important role in the production of capture fisheries, but many still live in poverty and face social challenges that threaten their welfare. This study aims to analyze the social resilience of small-scale fisher households and the factors that influence the social resilience of small-scale fisher households in Bengkulu City. The social resilience index of small-scale fisher households is based on four criteria, namely health, education, social capital and housing. The research location was chosen purposively, with a sample of 100 people selected using the accidental sampling method. The results showed that the social resilience index of small-scale fisher households in Bengkulu City was 66.65% because the index >50% was included in the socially resilient category with 89 households with socially resilient status. The dimensions of housing and health showed good results, while social capital and education needed to be improved. Factors that significantly influence the social resilience of small-scale fisher households in Bengkulu City are formal education, fisher income, and participation in fisher institutions. Policy implications include improving access and quality of education through training and improved facilities, as well as strengthening social capital through gotong royong and public space management. These efforts are important to sustainably improve the social resilience of fishermen.